Secular trends in sex ratios at birth in South America over the second half of the 20th century - Victor Grech (Brazilian Society of Pediatrics, 2013)
Objectives: Latitude gradients have been found in the male-female ratio at birth (M/F: male divided by total births), which is anticipated to be 0.515. Methods: Annual national male and female live births by country were obtained from the World Health Organization (WHO) and analysed with contingency tables. The continent was arbitrarily divided into two regions: a region 10° above the Equator to 20° below the Equator, and a second area 20° below the Equator. Results: This study analyzed 147,773,689 live births. An overall increasing trend in M/F was found for the region >20° (p < 0.0001) for the entire period. For the aggregate, a significant decrease was present for the period 1950-74 (p = 0.01) followed by a significant increase thereafter (p < 0.001). A latitude gradient was also noted, with more males being born in cooler (more Southern > 20° S) latitudes (p < 0.0001). There were 3,765,648 male births in excess of what was anticipated. Conclusion: The M/F ratio is increasing in South America, unlike the decline present in Europe and North America. This study also showed that M/F latitude gradients are similar to those previously reported in North America, with more males being born in cooler latitudes, contrary to the trends reported in Europe. The interplay of several poorly understood factors is likely.